KARAKTERISTIK ABU LAYANG (FLY ASH) DARI PLTU TANJUNG SELOR DAN POTENSINYA SEBAGAI PREKURSOR MATERIAL ALUMINOSILIKAT - Hayati, Nur; ‘Adany, Fildzah; Nugraeni, Crhistine Dyta; Syarif, Iif Ahmad; Kurniawati, Riskaviana (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2023)
Around 500 million tonnes of coal combustion by-products are produced annually, with Fly Ash accounting for about 70% of the by-product. Therefore, using Fly Ash is crucial because if it is not processed and utilized correctly, it can harm the environment and human health. The use of Fly Ash is strongly influenced by its characteristics, which are different for each source because it depends on the type of coal, combustion, and cooling conditions. Therefore, characterization was carried out in this study using XRF and XRD on Fly Ash from Tanjung Selor PLTU. Based on ASTM C618, PLTU Fly Ash Tanjung Selor is class F Fly Ash because the amount of SiO2+Al2O3+Fe2O3 is 71,4% (>70%) and the amount of CaO is 13,83% (<15%). The XRD results also show that Fe2O3 and SiO2 dominate the Fly Ash with the appearance of the peak of Fe2O3 (hematite) at 2θ = 33,44; 35,57; 43,27° (PDF 01-073-0603) and SiO2 (quartz) at 2θ = 20,81; 26,63; 50,14; 57,26; 68,34° (PDF 01-085-0335). The characteristics of this Fly Ash indicate that it has the potential as a precursor for the synthesis of zeolite X and P because it has a SiO2/Al2O3 ratio of 1,63. In addition, due to the dominant Si and Al content, Fly Ash has the potential as a geopolymer precursor; the dominant Fe content (27%) can also increase the geopolymer's development strength.